ML-14 Re-challenge and maintenance therapy of methotrexate for elderly PCNSL patients with low scored KPS - Yamaguchi, Takashi (Neurooncol Adv, 2020)
Purpose: The delayed neuronal toxicity after high dose methotrexate (HD-MTX) followed by radiotherapy (RT) is a serious problem for elderly primary CNS lymphoma patients. We started maintenance therapy (MT) with MTX after achieving complete remission (CR) to defer RT for elderly and poor Karnofsky Performance Scale (KPS) patients. Methods: We performed HD-MTX (3.5g/m2) therapy until achieving CR for the patients over 70 years whose KPS were equal to or less than 60%. After having CR, 3 courses of MT of MTX (3g/patient) for 3 weeks were introduced every 3–4 months for 2 years. At the time of recurrence, HD-MTX was repeated. But when CR was not achieved by HD-MTX alone, RT was introduced. Moreover, additional use of rituximab was considered if patients’ condition became better. Results: Number of patients was 9. Median age, median KPS, and median follow up periods were 73y.o. (71–78), 40% (30–60), and 14.0 months (1–55), respectively. CR rate was 78% and two patients were not achieved CR due to the adverse events (AEs) which were acute tubular necrosis and pneumocystis pneumonia. But meanwhile, there was no AE by MT. Median OS, median PFS, median time of radiation free period and delayed neuronal toxicity were 19.5 months (95%CI 3-NA), 5.0 months (95%CI 2–22), 2.5 months, and 8.2 months, respectively. Discussion: The results of this study might be inferior to other reports of elderly patients due to poor median KPS. And low introduction rate of MT was undesirable. However, once MT was introduced, MT itself was safe and easy to manage and the long-term prognosis was excellent. Conclusion: Rechallenge of HD-MTX and maintenance therapy of MTX might be promising but the problems of some serious AEs and low CR rate with HD-MTX alone should be resolved.